Early Psychological Therapy in Critical Illness - Karnatovskaia, Lioudmila V.; Philbrick, Kemuel L.; Parker, Ann M.; Needham, Dale M. (Seminars in Respiratory and Critical Care Medicine, 2016)
Survivors of critical illness often experience long-lasting impairments in mental, cognitive, and physical functioning. Acute stress reactions and delusional memories appear to play an important role in psychological morbidity following critical illness, and few interventions exist to address these symptoms. This review elucidates acute psychological stressors experienced by the critically ill. The effects of psychological stress and state of mind on disease are discussed using examples from the non–intensive care unit (ICU) literature, including a review of placebo and nocebo effects. After reviewing the effect of the mind on both psychological and physiological outcomes, we then focus on the role of memories—including their malleable nature and the consequences of false memories. Memory may play a role in the genesis of subsequent psychological trauma. Traumatic memories may begin forming even before the patient arrives in the ICU and during their state of unconsciousness in the ICU. Hence, practical interventions for redirecting patients' thoughts, such as positive suggestion techniques and actively involving patients in the treatment process as early as possible, are worthy of further investigation.
Keywords: psychological; critical illness; ICU